Measuring and explaining the changing nature of work - The Linked Personnel Panel enriched with administrative employment data (LPP-ADIAB) - Grunau, Philipp; Haepp, Tobias; Mackeben, Jan; Ruf, Kevin; Wolter, Stefanie (International Journal of Population Data Science, 2019)
In a rapidly changing world of work, policy-makers have new questions for evidence-based policy advice that go beyond what administrative data can provide. For example, the focus is on flexible forms of work or the permeability of the boundary between work and leisure time. Survey data can provide a good basis for answering these questions. In many respects, however, they do not come close to the representativeness and measuring accuracy of administrative data. Here the combination of survey data with administrative data can help to get the best out of two systems. On the one hand, objective information about the population is available and on the other hand, the survey data contain much more detailed information on a variety of topics. With the Linked Personnel Panel (LPP), the administrative data are used both for drawing a sample that is as undistorted as possible and for adjusting weighting factors. The LPP is a linked operational and employee data set that collects information on personnel instruments, corporate culture and work quality. Supplemented with the administrative data as LPP-ADIAB, we have advised policy makers on the relevance of home office for companies and employees. We know from the data of the employees whether their activity is suitable for home office. In the first step, these data are linked with the job information of the same employees from the administrative data. In the second step, we can transfer these values to the employees in Germany and estimate an undepleted homeoffice potential. With the help of the LPP-ADIAB, we were able to show the limited effect of a right to homeoffice and thus provided a comprehensive picture in a discussion led by a small group of supporters.